Disaster Preparedness and Resiliency as Predictors among Residents Situated in Landslide-Prone Areas in Brgy. Matina Crossing - Solano, Roel Nickelson M.; Catayas, Elaiza Faith N.; Laurnal, Kinah S.; Saranillo, Marc Joshua A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This research aims to determine the inter-relationship among the profile, disaster preparedness, and resiliency of the residents in Barangay 74-A Matina Crossing and what demographic profile significantly predicts resiliency as well as the disaster preparedness of the residents. It explores whether resiliency significantly predicts disaster preparedness among the identified residents. A survey was conducted on a convenience sample of 400 residents situated in a landslide-prone area in Barangay 74-A Matina Crossing using a 3-part structured questionnaire; the Demographic Profile of the residents, the Disaster Preparedness Index, and the Resiliency Scale. When grouped according to sex, it shows that 200 (50.0%) were males and 200 (50.0%) were females. The age groups have a total of 247 respondents (61.8%) with ages between 18-25 years old; 90 respondents (2.5%) with ages between 36-39 years old; and 63 respondents (15.8%) with ages between 50-60 years old. The overall mean of the level of disaster preparedness is 2.66 with a standard deviation of 0.30, indicating that the disaster preparedness of respondents is well-prepared. The respondents obtained the descriptive interpretation of true nearly all the time mean ratings on meaningfulness/Purpose, and the other six variables: Self-Efficacy, Hardiness, Adaptability/Flexibility, Regulation of Emotion and Cognition, and Coping, had often true mean ratings. Findings highlight the significant associations of demographic profiles, disaster preparedness, and resiliency, while regression results show that the demographic profile did not significantly predict the resiliency of the residents. However, only adaptability/flexibility significantly predicts the disaster preparedness of the identified residents.